(untitled) (Global Journal of Science Frontier Research, 1969)
In the present work the copolymerization of ε-caprolactone (CL) with propylene oxide (PO) uses proton exchanged Montmorillonite clay as initiator is reported. The effects of the amounts of Maghnite -H+ and the temperature on the synthesis of poly (ε-caprolactone-co- propylene oxide) were studied. The copolymer obtained was characterized by 1H-NMR spectroscopy.